PENGARUH EFISIENSI PENGELOLAAN KEARSIPAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KANTOR LURAH LANTORA KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Muhammad Syaeba (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This research was motivated by the problems found in the Lantora Urban Village Office, Polewali Subdistrict, Polewali Mandar District, namely there are still some indications that lead to low employee work productivity because the efficiency of archival management has not been maximized. This can be seen from the existence of archives that are not stored in place, stacked in filing cabinets and warehouses, causing the archive to be quickly damaged and difficult to find. As a result, there are still jobs that are not completed on time so that the results of work achieved are not maximized. Therefore, it is necessary to have efficient, good and orderly archival management so that it can make it easier for employees to store and find. Archive arrangement is one aspect that must be applied in achieving office goals in order to support increased office work productivity.